Global agenda a jej význam pre budúci vývoj sociálnej práce - Levická, Jana; Levická, Katarína (Univerzita Pardubice, 2013)
This paper reports about the most significant document that was prepared in the environment of social work over the past three decades. First, the authors provide information about creation and content of this document, then they point to the impact of the document on the discussion about current challenges and future direction of social work. The paper also propose a new definition of social work which is expected to be formally adopted at the joint World Conference on Social Work, Education and Social Development to be held in Melbourne in July 2014 and explains the link between the Global Agenda and the new definition of social work. The authors meditate further on why this document remains almost unknown for the Czech and Slovak social workers, consider the potential of the Global Agenda document and discuss it from the perspective of the profession identity.
Global agenda and its impact on future development of social work
Keywords: global agenda; social work; social justice; definition of social work